PHARMACOEPIDEMIOLOGICAL ANALYSIS OF THE TREATMENT OF PAROXYSMAL AND PERSISTENT ATRIAL FIBRILLATION IN EVERY DAY CLINICAL PRACTICE - I. V. Graifer; O. V. Reshet'ko; N. V. Furman (Рациональная фармакотерапия в кардиологии)
Aim. To analyze current clinical practice in the treatment of atrial fibrillation (AF) in emergency care department of multidisciplinary hospital in 2008-2009. Material and methods. Retrospective continuous pharmacoepidemiology study was carried out. Hospital history sheets of the patients admitted to the emergency care department in the period from 01.01.2008 to 31.12.2009 were analyzed. Results. Physicians of emergency care department mainly chose strategy of sinus rhythm restoration and maintenance in patients with paroxysmal and persistent AF . To implement this strategy pharmacological cardioversion was performed in patients with stable hemodynamics. The most frequently used medicine for pharmacological cardioversion was procainamide (60% of all prescriptions). Its efficacy was about 50% as compared with this of 80% for amiodarone and propafenone. In order to maintain sinus rhythm monotherapy with beta-blockers or amiodarone was preferred. Conclusion. Overall, AF treatment corresponded to current guidelines. Physicians preferred strategy of sinus rhythm restoration and maintenance.